EEG neurofeedback and isolation stressor. A systematic review - Kacper Gotner; Marcin Dornowski (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2022)
Introduction. One of the factors increasing the body's response to a stressful situation is isolation. The feeling of loneliness in isolation can be caused by biological, psychological or medical factors. Material and methods: This paper is a review of publications issued in 2009-2021, the most up-to-date in terms of information on the topic of stress and its links with EEG neurofeedback. Results: 5 publications on stress caused by isolation and the reaction of the human body in a stressful situation were selected. The papers were selected based on the use of EEG neurofeedback in reducing the body's stress reactions to isolation. Conclusions: There is a lack of studies in the available literature describing the direct application of EEG neurofeedback in the reduction of stress caused by isolation despite demonstrating its potential in individual studies.